A training program to improve the physical abilities related to the offensive stroke skill in volleyball players. - Mahdi, Prof.Dr.Ali Ghadhban; Jassim, Asst.L.Riyam Emad; Shabeeb, Prof.Dr.Huda Badawi (Sulaimani Journal for Humanities, 2026)
The research aims to develop a training program to improve the physical abilities related to the attacking stroke skill in volleyball players by (identifying the physical abilities related to the attacking stroke skill in volleyball, designing a proposed program to improve the physical abilities related to the attacking stroke skill in volleyball). The researcher used the experimental method as it is suitable for the nature of the research and the researcher used the experimental design with pre- and post-tests for one experimental group. The researcher selected a random sample of (20) players registered in the Iraqi Volleyball Federation. One of the most important results was that the proposed training program led to an improvement in the physical abilities related to (speed-strength of the legs and arms, accuracy, agility, back flexibility, movement speed, and shoulder flexibility
Keywords: Program; physical abilities; offensive strike